A PILOT STUDY IN EKAKUSHTHA W.S.R. TO PSORIASIS WITH SHODHAN CHIKITSA I.E. VAMANA AND VIRECHANA - Derashri, Bhavin; Katariya, Paresh A.; Gatfane, Rupali (International Journal of Research -GRANTHAALAYAH, 2018)
The word ‘Kushta’ is a broad term, which covers almost all the skin diseases. Kushtha is produced invariably by the vitiation of the seven factors i.e. 3 Doshas and 4 Dushyas But different types of pain, colour, shape, specific manifestation etc. are found in Kushtha because of Anshanshakalpana of the Doshas. Accordingly, Charaka explained Kushthas are in fact of innumerable types, but for systemic study they are classified into two major groups 7 Maha Kushtha & 11 Kshudra Kushtha. Ekakushtha is one of the Kshudra Kushtha. It is the prime among the Kshudra Kushtha, hence Bhavaprakasha mention it as Ekakushtha. Almost all symptoms are vata-kapha predominant & even tri dosha involvement and for this Shodhana Chikitsa i.e. vamana and virechana are the best line of treatment. We can use these modality as per requirement. Kandu get relieved completely (100 ٪) in all both the groups. Low effect was seen in Aswedanam i. e. (33.33٪), Matsyashalklopama was reduced and shows 83.33٪ relief, Rukshata shows 91.66٪ relief. Highly significant result found after shodhan (Vamana & Virechana) & marked improvement was seen in group A & B. it shows overall ayurvedic modality gives very good result in Ekakushtha.